QUEST FOR GLOBAL PEACE: CONTEXTUALIZING THE ROLE OF PROPHET MUḤAMMAD’S SUNNAH - Malik, Mohd. Ashraf (Universitas Islam Indonesia, 2024)
The world we live in has everything to offer but peace. While the Western and European countries wrestle with calamities like sexual anarchy, drug abuse, broken marital relationships, the Asian countries are torn-apart by violence, extremism and civil wars. The race for armaments among nations, misuse of nuclear weapons, miscarriage of justice, ruthless use of military force, and exploitation of natural resources by powerful countries is all happening under the nose of United Nation’s Security Council and the International Court of Justice. The greatest challenge staring at humanity is to seek the underlying cause of violence in their societies and global levels. It requires a world-wide collaboration and collective efforts to ensure enduring peace at local and international levels. To make peace a reality, humanity has to seek for the harmony at grass-root levels. In this context, the role of one of the greatest benefactors of humanity-Prophet Muḥammad (PBUH) is productive and comprehensive. The Prophet (PBUH) ushered peace at all the levels of the society as was reflected in his conduct and behavior. In this paper, I seek to contextualize the role of Prophet Muḥammad (PBUH) in building up the peace within humanity. Some glaring examples from the life of the Prophet (PBUH) may be cited that will help in addressing the grave challenges of insecurity and violence in the world. The paper suggests for the adoption of the practices and principles of Prophet Muḥammad (PBUH) that would go a long way to nurture peace among individuals and societies.